Effects of Increasing Non-Fiber Carbohydrate to Neutral Detergent Fiber Ratio on Rumen Fermentation and Microbiota in Goats - Da-cheng LIU; Xiang-li ZHOU; Pei-ting ZHAO; Min GAO; Hao-qi HAN; Hong-lian HU (Journal of Integrative Agriculture)
Six rumen-cannulated lactating Guanzhong goats were used to investigate changes in ruminal fermentation pattern and the microbiota following a subacute ruminal acidosis (SARA) inducing procedure. Induction of SARA was performed by increasing dietary non-fiber carbohydrate (NFC) to neutral detergent fiber (NDF) ratio from 1.02 (stage 1) to 1.24 (stage 2), 1.63 (stage 3) and 2.58 (stage 4). A dynamic pH monitoring system, real-time fluorescent quantitative PCR and conventional anaerobic culture were used to assess changes in ruminal pH and microbiota. Results indicated that rumen fermentation patterns changed significantly with increased NFC: NDF ratio. The decline in ruminal pH was caused by increased ruminal total volatile fatty acids (TVFA), which was mainly attributed to a significant increase in ruminal butyrate, rather than the accumulation of ruminal lactic acid. In addition, in the course of SARA, the number of rumen microoganisms altered significantly, with increases in ruminal amylolytic bacteria, Lactobacilli, Streptococcus bovis and Megasphaera elsdenii, the latter particularly dramatically indicating that it may be the main factor responsible for the increase in butyrate, and decrease in protozoa.